Modification of the existing maximum residue levels for difenoconazole in various crops - Brancato, Alba (EFSA J, 2018)
In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant BASF SE submitted a request to the competent national authority in the United Kingdom to modify the existing maximum residue levels (MRLs) for the active substance difenoconazole in various crops. The data submitted in support of the request were found to be sufficient to derive MRL proposals for all crops under consideration. Adequate analytical methods for enforcement are available to control the residues of difenoconazole in plant matrices under consideration. The estimated long‐term and short‐term intake to residues of difenoconazole resulting from the existing and the intended uses did not exceed the toxicological reference values established for the active substance difenoconazole. The consumer exposure assessment has to be considered provisional as the impact of a potentially different isomer composition in the residues of difenoconazole on this risk assessment is currently unknown and has to be reconsidered when data on possible preferential metabolism/degradation of the four stereo isomers of difenoconazole in plants is available and guidance on a risk assessment approach for residues containing isomers is implemented.